Controlled outcome studies of child clinical hypnosis - Adinolfi, Barbara; Gava, Nicoletta (Acta Biomedica Atenei Parmensis, 2013)
Background Hypnosis is defined as “as an interaction in which the hypnotist uses suggested scenarios (“suggestions”) to encourage a person’s focus of attention to shift towards inner experiences”. Aim of the work The focus of this review is to summarize the findings of controlled outcome studies investigating the potential of clinical hypnosis in pediatric populations. We will examine the following themes: anesthesia, acute and chronic pain, chemotherapy-related distress, along with other specific medical issues. Results Hypnosis is an effective method to reduce pain and anxiety before, during and after the administration of anesthetics, during local dental treatments, invasive medical procedures and in burn children. Hypnosis can be successfully used to manage recurrent headaches, abdominal pain, irritable bowel syndrome and chemotherapy-related distress. Hypnosis has an important role in managing symptoms and improving the quality of life of children suffering from asthma and cystic fibrosis and in facilitating the treatment of insomnia in school-age children. Finally, hypnosis can be effectively used for the treatment of some habitual disorders such as nocturnal enuresis and dermatologic conditions, including atopic dermatitis and chronic eczema Conclusions Clinical hypnosis seems to be a useful, cheap and side-effects free tool to manage fear, pain and several kinds of stressful experiences in pediatric populations. Children who receive self-hypnosis trainings achieve significantly greater improvements in their physical health, quality of life, and self-esteem.